Can a noisy venue be bad for comedy? - Drew Gorenz; Norbert Schwarz (PLoS ONE, 2025)
People hear jokes live and pre-recorded in a variety of settings, from comedy clubs, bars, outdoor venues, cafes, to their own home or car. While a lot of research has analyzed the significance of the content of jokes, we know less about the significance of the setting one hears them in. Some settings can have interfering background noise or poor acoustics, reducing an audience’s ease of processing heard jokes. Would this affect how funny the jokes seem? Two experiments with audio clips of stand-up comedy performances show that participants found jokes less funny when background noise interfered with their listening.